The lived experience of depression: a bottom-up review co-written by experts by experience and academics - Fusar-Poli, Paolo; Estradé, Andrés; Stanghellini, Giovanni; Esposito, Cecilia Maria; Rosfort, René; Mancini, Milena; Norman, Peter; Cullen, Julieann; Adesina, Miracle; Jimenez, Gema Benavides; da Cunha Lewin, Caroline; Drah, Esenam A.; et al. (World psychiatry, 2023)
We provide here the first bottom-up review of the lived experience of depression, co-written by experts by experience and academics. First-person accounts within and outside the medical field were screened and discussed in collaborative workshops involving numerous individuals with lived experience of depression, family members and carers, representing a global network of organizations. The material was enriched by phenomenologically informed perspectives and shared with all collaborators in a cloud-based system. The subjective world of depression was characterized by an altered experience of emotions and body (feeling overwhelmed by negative emotions, unable to experience positive emotions, stuck in a heavy aching body drained of energy, detached from the mind, the body and the world); an altered experience of the self (losing sense of purpose and existential hope, mismatch between the past and the depressed self, feeling painfully incarcerated, losing control over one's thoughts, losing the capacity to act on the world; feeling numb, empty, non-existent, dead, and dreaming of death as a possible escape route); and an altered experience of time (experiencing an alteration of vital biorhythms, an overwhelming past, a stagnation of the present, and the impossibility of the future). The experience of depression in the social and cultural context was characterized by altered interpersonal experiences (struggling with communication, feeling loneliness and estrangement, perceiving stigma and stereotypes), and varied across different cultures, ethnic or racial minorities, and genders. The subjective perception of recovery varied (feeling contrasting attitudes towards recovery, recognizing recovery as a journey, recognizing one's vulnerability and the need for professional help), as did the experience of receiving pharmacotherapy, psychotherapy, and social as well as physical health interventions. These findings can inform clinical practice, research and education. This journey in the lived experience of depression can also help us to understand the nature of our own emotions and feelings, what is to believe in something, what is to hope, and what is to be a living human being.